Factors affecting the Haemophilia Joint Health Score in children with severe haemophilia. (28th March 2013) - Bladen, M.; Main, E.; Hubert, N.; Koutoumanou, E.; Liesner, R.; Khair, K.
Summary Joint damage from bleeding episodes leads to physical or functional limitations in people with haemophilia. Various factors may influence the frequency and severity of joint damage. This study examined whether age, prophylaxis, history of high‐titre inhibitors (HTI) and bleeding events influenced the Haemophilia Joint Health Score (HJHS) in children. Medical and physiotherapy notes of boys with severe haemophilia, aged 4–18 years, were reviewed to identify factors associated with increased HJHS. The HJHS of 83 boys (median age: 11) ranged from 0 to 25, with 44/83 (53%) having a score of zero. The median HJHS was 0 (mean 2.6). In the non‐HTI group, the HJHS for boys on late prophylaxis was 2.68 times higher than those who started early and the HJHS was on average 10% higher for every additional recent bleed. In this group the odds of having a zero score fell by 30% for every year increase in age. Boys with a history of HTI had higher HJHS scores than the non‐HTI group, and age, number of recent bleeds and tolerized status were positively associated with HJHS. The score rose on average by 28% for every year of age and by 76% for non‐tolerized boys. This study provides further evidence supporting early prophylaxis use and the importance of immune tolerance therapy. The HJHS is a useful tool for identifying and tracking changes in joint health with respect to therapy or disease progression. With improvements in haemophilia treatment, the disproportionate number of zero scores will continue to make interpretation of the HJHS challenging.